2018
DOI: 10.22454/fammed.2018.875510
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Racism in Medical Education

Abstract: Results suggest that this workshop changed knowledge and attitudes about racism and health inequities. Findings also suggest this workshop improved confidence in teaching learners to reduce racism in patient care. The authors recommend that curricula continue to be developed and disseminated nationally to equip faculty with the skills and teaching resources to effectively incorporate the discussion of racism into the education of health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 4 publications
1
92
0
1
Order By: Relevance
“…Methods for improving health disparities training for healthcare providers include building their knowledge of health disparities and effective interventions, improving their communication skills and increasing their understanding of how attitudes and unconscious biases may impact clinical encounters [8,26]. These methods align with our findings that more than 90% of residents reported that knowing what interventions help to improve the disparity and knowing how to change their practice to help close gaps in care would help them feel more prepared to discuss health disparities with patients.…”
Section: Discussionsupporting
confidence: 65%
“…Methods for improving health disparities training for healthcare providers include building their knowledge of health disparities and effective interventions, improving their communication skills and increasing their understanding of how attitudes and unconscious biases may impact clinical encounters [8,26]. These methods align with our findings that more than 90% of residents reported that knowing what interventions help to improve the disparity and knowing how to change their practice to help close gaps in care would help them feel more prepared to discuss health disparities with patients.…”
Section: Discussionsupporting
confidence: 65%
“…Classroom sessions formed another part of the intervention. Privilege activities 16,21 illustrated how race, ethnicity, and other socioeconomic and cultural factors influenced learners' experiences in everyday life. TASF used the privilege activity from the Toolkit, 16 with modification for space (Table 1).…”
Section: Interventionmentioning
confidence: 99%
“…Privilege activities 16,21 illustrated how race, ethnicity, and other socioeconomic and cultural factors influenced learners' experiences in everyday life. TASF used the privilege activity from the Toolkit, 16 with modification for space (Table 1). OUFCM's planned privilege session was delayed due to acts of explicit racism affecting residents and their families.…”
Section: Interventionmentioning
confidence: 99%
“…An example of this last strategy can be seen in a recent publication on addressing the topic of racism in medical education (see table 1). 2 6…”
Section: Introductionmentioning
confidence: 99%